Alokasi Pengeluaran Rumah Tangga Penyadap Getah Pinus di Desa Somagede, Kabupaten Kebumen Jawa Tengah - S. Andy Cahyono; Nunung Puji Nugroho; Yonky Indrajaya (Fakultas Kehutanan Universitas Gadjah Mada, 2007)
Expenditure Allocation of Resin Tapper`Households in Somagede Village, Kebumen Regency, Central JavaPine forest has contributed to local people economy, especially the resin tappers. Increasing income will raise the household expenditure both of consumptive and productive needs. This research was aimed to assess the expenditure allocations of resin tappers’ household and to identify the factors affecting them.Survey method was adopted in this research to collect the primary data of 30 respondents. The collected data was analyzed both quantitatively and qualitatively. Multiple linear regression model was applied to figure out the factors affecting the expenditure allocations of resin tappers’ household.The results of the study indicated that the expenditure of resin tappers’ household reached to Rp 2,366,459 per annum and 58,08% of it was food and beverage expenditure. The expenditure allocations were affected significantly by tappers’ age, food and beverage expenditure, and farm land size. The tappers’ age, food and beverage expenditure had a positive effect whereas farm land size had a negative effect on the household expenditure.